Putin's Russia economy, defense and foreign policy - Rosefielde, Steven (World Scientific, 2020)
"This volume seeks to fill the vacuum created by the Joint Economic Committee of Congress's decision to cease publishing comprehensive assessments of Russia's performance and potential. It provides readers with authoritative descriptions of Russia's economy, military prowess and international ambitions. The volume does not settle controversies, but does provide readers with an objective basis for assessing Russia's prospects without the distortions caused by fake news and disinformation wars"--